2023
DOI: 10.1061/jaeied.aeeng-1505
|View full text |Cite
|
Sign up to set email alerts
|

BIM-Enabled Design Collaboration Processes in Remote Architectural Practice and Education in Australia

Abstract: Remote teamwork has become critical to the communicative and collaborative operations of architectural practice and education in Australia. Consequently, building information modeling (BIM) processes, which are core to both sharing and producing architectural designs, are evolving in response. The aim of this paper is to examine and identify ways to improve BIM-enabled design collaboration processes in architectural practice and education. Using data from semi-structured open-ended interviews (n = 25) undertak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
0
3
0
2
Order By: Relevance
“…3. An integrated model of BIM-enabled design collaboration processes, source: own study based on [16] This model can be employed as an assessment framework for evaluating BIM practices, allowing for a sequential examination of each theme and process. Conversely, architectural firms or teams can iteratively apply specific themes to enhance BIM processes, thus meeting the requirements of interconnected themes.…”
Section: Resultsmentioning
confidence: 99%
“…3. An integrated model of BIM-enabled design collaboration processes, source: own study based on [16] This model can be employed as an assessment framework for evaluating BIM practices, allowing for a sequential examination of each theme and process. Conversely, architectural firms or teams can iteratively apply specific themes to enhance BIM processes, thus meeting the requirements of interconnected themes.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have demonstrated the effectiveness of virtual environments for managing models at various levels of detail, safety training, site layout planning, collision detection, and more [32][33][34]. Research has also been conducted on collaboration and model management in virtual environments among different stakeholders [35], as well as on decision-making aspects [36] and educational contexts [37][38][39].…”
Section: Background and Challenges To Implementing Immersivenessmentioning
confidence: 99%
“…OpenBIM provides a potential solution to build an open and neutral environment for the exchange of information, allowing for better interoperability among the diverse software tools used in the industry [41,42]. By embracing OpenBIM standards, the industry can move towards a more collaborative and efficient way of working, overcoming the barriers of proprietary formats and fostering a more inclusive approach to project development [43][44][45][46][47].…”
Section: Data Communication For Bim Collaborative Designmentioning
confidence: 99%